Investigating the Impact of Female Directors on Firm Financial Performance: Empirical Evidence from China - HE, Qiuning (2019)
The board of directors is always considered a key issue in corporate governance. There are many scholars that study the relationship between the composition of a diversified board of directors and firm financial performance. The topic of gender equality on boards has gradually attracted the attention of scholars in recent years. Although academic research into US and European companies have made significant progress in recent years, there are still few scholars studying this topic in China. Therefore, this dissertation collected three-year panel data on Chinese-listed firms and analyzed how gender factors can influence board behavior and firm financial outcomes. This dissertation used the board meeting frequency to measure board behavior. In terms of financial measurements, this dissertation selected ROA (Return on assets) and Tobin’s Q. In order to control the effect of heterogeneity on our results, this dissertation employed the fixed effects model to analyze the data. Our results show that the higher the level of board gender diversity, the more board meetings are held during a year. Besides, the proportion of female directors and the Blau index have a significantly positive relationship with ROA. By using Tobin’s Q to analyze financial outcomes, this dissertation found a positive but non-significant result. Currently, Chinese boards are dominated by men, but it is believed that companies should pay more attention to candidates’ abilities, rather than just focusing on gender. Our findings make contributions to the promotion of gender equality in China and the improvement in firm financial performance. From the perspective of sociology, increasing the proportion of female board members is a very important action to promote gender equality. In Chinese culture, it is difficult for women to participate in the firm decision-making process. Therefore, this research can be helpful to alleviate gender discrimination. From the perspective of business management, increasing the proportion of women can improve firm financial performance.